Fluorescence mechanism switching from ICT to PET by substituent chemical manipulation: Macrophage cytoplasm imaging probes. (April 2020) - Fueyo-González, Francisco; González-Vera, Juan A.; Alkorta, Ibon; Infantes, Lourdes; Jimeno, M. Luisa; Fernández-Gutiérrez, Mar; González-García, M. Carmen; Orte, Angel; Herranz, Rosario
Abstract: The lack of polarity sensing fluorophores with OFF-ON features when increasing the environment polarity has limited the monitoring of biological processes that involve an increase in local hydrophilicity. In this work, replacement of a hydroxyl group by a dimethylamino group transformed solvatochromic ICT naphthalimide- and quinolimide-based fluorophores into reversed solvatochromic ones, with higher emission in polar than in apolar environments. Excited-state dynamics studies, TD-DFT calculations, X-ray and NMR support the existence of a folded conformation for the 2-(dimethylamino)ethyl chain upon the imide ring in apolar solvents, where the dimethylamino group would quench the fluorescence by a PET effect, while in polar solvents the chain has an extended conformation, where the PET is hindered. These PET fluorophores have given rise to H2 O and pH sensors in organic solvents as well as to bright macrophage cytoplasm imaging probes. Graphical abstract: OFF-ON polarity sensing PET fluorophores were obtained by simple substituent manipulation of solvatochromic (ICT) fluorophores. This switching led to H2 O and pH sensors and cell cytoplasm imaging probes. Image 1 Highlights: Naphthalimide and quinolimide-based fluorophores have been prepared. ICT fluorophores are switched to OFF-ON polarity sensing PET fluorophores. TRES, TD-DFT calculations, X-ray and NMR support a PET fluorescence mechanism. The dyes behave as OFF-ON H2 O and pH fluorescence sensors. Macrophage cytoplasm fluorescence imaging probes are obtained.